2001
DOI: 10.1177/101269001036003003
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnography of Pain and Injury in Professional Rugby Union

Abstract: In the professional game of Rugby Union the elimination of injury to players has become a paramount performative, and therefore financial, concern. The recognition that professional contact sports entail the potential for significant injury is becoming increasingly evident in the disciplines of sports medicine and the sociology of sport. Among the complex of factors that comprise the habitus of a rugby club will be the expectation and accommodation of factors relating to injury. This article makes conceptual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 27 publications
5
67
0
7
Order By: Relevance
“…There are also certain cultural groups and subcultures in which the notion of stoicism in the face of pain is valued. These may be termed occupational cultures of stoicism, such as those found among male and female athletes (Howe, 2001;Roderick, 2006;Turner and Wainwright, 2003). In the majority of these studies stoicism is seen simply as not complaining.…”
Section: Culture and Geographies Of Stoicismmentioning
confidence: 99%
“…There are also certain cultural groups and subcultures in which the notion of stoicism in the face of pain is valued. These may be termed occupational cultures of stoicism, such as those found among male and female athletes (Howe, 2001;Roderick, 2006;Turner and Wainwright, 2003). In the majority of these studies stoicism is seen simply as not complaining.…”
Section: Culture and Geographies Of Stoicismmentioning
confidence: 99%
“…An emergent field of research focuses on pain and injury as it relates to sports and male athletes (Messner 1996;Nixon 1992;Young et al 1994;White et al 1995;Howe 2001Howe , 2004. Extensive research by Nixon has found that sports promote a "culture of risk" where injury is normalized (1992).…”
mentioning
confidence: 99%
“…Despite several studies examining the heavy physiological requirements of rugby (e.g., Deutsch, Kearney, & Rehrer, 2002;Deutsch, Maw, Jenkins, & Reaburn, 1998;Reilly, 1997) and factors contributing to the frequency and severity of injuries in it (e.g., Howe, 2001;Lee & Garraway, 2000;Lee, Myers, & Garraway, 1997), little is known about those who play the game professionally in terms of their psychological attributes. Thus, the present research is timely, given that a performer's psychological response to competition is thought to depend largely on the characteristics and requirements of the sport (Krane & Williams, 1987).…”
mentioning
confidence: 99%